2017
DOI: 10.1080/14397595.2017.1337288
|View full text |Cite
|
Sign up to set email alerts
|

Detection of synovial inflammation in rheumatic diseases using superb microvascular imaging: Comparison with conventional power Doppler imaging

Abstract: SMI was more sensitive in detecting synovial inflammation than cPDI in patients with RA. SMI could be a potentially useful imaging modality for accurately diagnosing and monitoring the disease activity of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…From our standpoint, SMI appears to be an extremely robust and reliable technique in the setting of neonatal ultrasound. Since initial reports in March 2016 [14], SMI has been mainly used in oncologic conditions (especially breast lesions) [2226], infectious diseases [16, 27, 28], gastrointestinal disorders [2932], obstetric ultrasound [33, 34], musculoskeletal [35], vascular [36], and endocrine disorders [14]. In paediatric imaging, SMI has been used to detect direction of urinary flow in patients with vesico-urethral reflux without the use of contrast [16] and to demonstrate differences in vascular flow grades between normal and undescended testes, which were invisible by Power Doppler [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…From our standpoint, SMI appears to be an extremely robust and reliable technique in the setting of neonatal ultrasound. Since initial reports in March 2016 [14], SMI has been mainly used in oncologic conditions (especially breast lesions) [2226], infectious diseases [16, 27, 28], gastrointestinal disorders [2932], obstetric ultrasound [33, 34], musculoskeletal [35], vascular [36], and endocrine disorders [14]. In paediatric imaging, SMI has been used to detect direction of urinary flow in patients with vesico-urethral reflux without the use of contrast [16] and to demonstrate differences in vascular flow grades between normal and undescended testes, which were invisible by Power Doppler [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…They are usually associated with rheumatologic diseases. In one of them, the authors found significantly higher total SMI scores patients with rheumatic diseases and these scores significantly correlated with the levels of serum C‐reactive protein and matrix metalloproteinase‐3 . In another study with rheumatoid arthritis (RA), they demonstrated that SMI was more sensitive than power Doppler imaging for detecting synovial vessel signals of the hand joint in patients with RA in clinical remission .…”
Section: Discussionmentioning
confidence: 98%
“…Musculoskeletal US can monitor angiogenesis within musculoskeletal soft tissues and facilitate the evaluation of disease activities . In recent studies, SMI was used to assess arthritis, lateral epicondylitis, and carpal tunnel syndrome (CTS) . Lim et al assessed the efficacy of SMI in detecting joint inflammation and found that SMI had the ability to detect mild inflammation that was difficult to observe by PDFI, with improved resolution and sensitivity (Figure ).…”
Section: Superb Microvascular Imaging For the Assessment Of Musculoskmentioning
confidence: 99%
“…40 In recent studies, SMI was used to assess arthritis, lateral epicondylitis, and carpal tunnel syndrome (CTS). [41][42][43][44][45] Lim et al 43 assessed the efficacy of SMI in detecting joint inflammation and found that SMI had the ability to detect mild inflammation that was difficult to observe by PDFI, with improved resolution and sensitivity (Figure 4). This result was confirmed by a study conducted by Yokota et al 41 In their study, SMI scores were much higher than PDFI scores in patients with rheumatoid arthritis.…”
Section: Superb Microvascular Imaging For the Assessment Of Musculoskmentioning
confidence: 99%
See 1 more Smart Citation